Trichoderma harzianum prevents red kidney bean root rot by increasing plant antioxidant enzyme activity and regulating the rhizosphere microbial community - Guo, Zhifen; Zhang, Jiaxing; Liu, Zhibin; Li, Yu; Li, Meng; Meng, Qiuxia; Yang, Zhiping; Luo, Yuan; Zhang, Qiang; Yan, Min (Frontiers in Microbiology, 2024)
Root rot is one of the main reasons for yield losses of red kidney bean (Phaseolus vulgaris) production. Pre-inoculation with Trichoderma harzianum can effectively lower the incidence of red kidney bean root rot. In this study, four treatments including CK (control), Fu13 (Fusarium oxysporum), T891 (T. harzianum) and T891+Fu13 (T. harzianum+F. oxysporum) were arranged in a pot experiment to investigate the effect of T891 on the incidence and severity of root rot, plant growth, and changes of defense enzyme activity in red kidney bean plants. High-throughput sequencing was used to analyze the diversity and composition of the rhizosphere microbiota, and co-occurrence network was analyzed. The results showed that when compared to the Fu13 group, pre-inoculation with T891 reduced the incidence and severity of red kidney bean root rot by 40.62% and 51.87% (p<0.05), increased the root length, shoot length, total dry biomass by 48.63%, 97.72%, 122.17%. upregulated activity of super-oxide dismutase (SOD), peroxidase (POD), catalase (CAT) by 7.32%, 38.48%, 98.31% (p<0.05), and reduced malondialdehyde (MDA) by 23.70% (p<0.05), respectively. Microbiological analyses also showed that F. oxysporum reduced alpha diversity resulting in alteration the composition of the rhizosphere microbial community in red kidney bean. T891 significantly reduced abundance of F. oxysporum, allowing the enrichment of potentially beneficial bacteria Porphyrobacter (ASV 46), Lysobacter (ASV 85), Microbacteriaceae (ASV 105), and Gemmatimonas (ASV 107), resulting in a more stable structure of the microbial network. The results of random forest analysis further revealed that ASV 46 (Porphyrobacter) was the primary influencing factor for the incidence of root rot after inoculation with T891, while ASV 85 (Lysobacter) was the primary influencing factor for the biomass of red kidney bean. In conclusion, T. harzianum promotes the growth of red kidney bean and inhibits root rot by improving plant antioxidant enzyme activity and regulating the rhizosphere microbial community.